Program sehari bersama Fakulti Kejuruteraan, 2003 - Universiti Malaysia Sarawak, Faculty of Engineering (Universiti Malaysia Sarawak (UNIMAS), 2003)
One Day programmed with Faculty of Engineering events. The purposed was to strengthen the relationship between the staff and students in the faculty.